Pediatric nonaortic arterial aneurysms - Davis, Frank M; Eliason, Jonathan L; Ganesh, Santhi K; Blatt, Neal B; Stanley, James C; Coleman, Dawn M (Journal of vascular surgery, 2016)
Pediatric arterial aneurysms are extremely uncommon. Indications for intervention remain poorly defined and treatments vary. The impetus for this study was to better define the contemporary surgical management of pediatric nonaortic arterial aneurysms. A retrospective analysis was conducted of 41 children with 61 aneurysms who underwent surgical treatment from 1983 to 2015 at the University of Michigan. Arteries affected included: renal (n = 26), femoral (n = 7), iliac (n = 7), superior mesenteric (n = 4), brachial (n = 3), carotid (n = 3), popliteal (n = 3), axillary (n = 2), celiac (n = 2), ulnar (n = 2), common hepatic (n = 1), and temporal (n = 1). Intracranial aneurysms and aortic aneurysms treated during the same time period were not included in this study. Primary outcomes analyzed were postoperative complications, mortality, and freedom from reintervention. The study included 27 boys and 14 girls, with a median age of 9.8 years (range, 2 months-18 years) and a weight of 31.0 kg (range, 3.8-71 kg). Multiple aneurysms existed in 14 children. Obvious factors that contributed to aneurysmal formation included: proximal juxta-aneurysmal stenoses (n = 14), trauma (n = 12), Kawasaki disease (n = 4), Ehlers-Danlos type IV syndrome (n = 1), and infection (n = 1). Preoperative diagnoses were established using arteriography (n = 23), magnetic resonance angiography (n = 6), computed tomographic arteriography (n = 5), or ultrasonography (n = 7), and confirmed during surgery. Indications for surgery included risk of expansion and rupture, potential thrombosis or embolization of aneurysmal thrombus, local soft tissue and nerve compression, and secondary hypertension in the case of renal artery aneurysms. Primary surgical techniques included: aneurysm resection with reanastomsis, reimplantation, or angioplastic closure (n = 16), interposition (n = 10) or bypass grafts (n = 2), ligation (n = 9), plication (n = 8), endovascular occlusion (n = 3), and nephrectomy (n = 4) in cases of unreconstructable renal aneurysmal disease. Later secondary operations were required to treat stenoses at the site of the original aneurysm repairs (n = 2) and new aneurysmal development (n = 1). Postoperative follow-up averaged 47 months (range, 1-349 months). No major perioperative morbidity and no mortality was encountered in this experience. Pediatric arterial aneurysms represent a complex disease that affects multiple vascular territories. Results of the current series suggest that individualized surgical treatment, ranging from simple ligations to major arterial reconstructions, was durable and can be undertaken with minimal risk.